Awareness of family physicians towards antihistamines - Sumaya Zeerak; Kiran Godse; Sujit Kumar (Wolters Kluwer Medknow Publications, 2019)
Background: Antihistamines are one of the commonly prescribed groups of drugs for allergic disorders and pruritus. They are broadly grouped into two generations, the second-generation ones being more effective and with less side effects. The family physicians frequently use antihistamines as patients contact them initially for their problem. It will be interesting to know the mode of selection of antihistamines by them. Materials and Methods: The study was carried out on a sample of 100 family physicians. Primary data were collected from them after taking informed consent. A pre-validated questionnaire regarding knowledge, awareness, and prescribing schedule of antihistamines was filled up. The data were then analyzed with suitable statistical tests. Results: Almost 73% of physicians prescribed second-generation antihistamines, while 27% prescribed the first-generation ones. Only 15% of them were aware about the ARIA and GA2LEN guidelines and their recommendations for prescribing second-generation antihistamines over the older first-generation antihistamines, while 85% had not heard about them previously. A minimum 7% of practitioners revealed that they updosed the same drug four times in the treatment of urticaria, while 93% did not do it. Conclusion: Even though a sizeable percentage of family physicians prescribed second-generation antihistamines, most of them were not aware of their dosing guidelines.